BLOB PARAMETERS OF ACCRETION STREAMS IN MAGNETIC CATACLYSMIC VARIABLES - Shakhovskoy, N. M.; Andronov, I. L.; Kolesnikov, S. V.; Halevin, A. V. (Одеські астрономічні публікації, 2017)
Results of investigations of the autocorrelation functions for two magnetic cataclysmic variables BY Cam and QQ Vul are presented. Significant variations of this characteristic are detected. They are interpreted as caused by variations of the blob length or by changes of the accretion column height. For the first time, the dependence "shot noise decay time - circular polarization" was discovered.